2019
DOI: 10.1111/jgs.15783
|View full text |Cite
|
Sign up to set email alerts
|

Do Differences in Spatiotemporal Gait Parameters Predict the Risk of Developing Depression in Later Life?

Abstract: Background/Objectives There is growing interest in the association between gait disturbance and depression in later life. The aim of this study is to clarify the longitudinal relationship between specific gait parameters and incident depression within a population‐representative sample of older people. Design Longitudinal analysis of spatiotemporal gait parameters at baseline (wave 1) and incident depression at 2 and 4 years (waves 2/3). Logistic regression models were used to assess the relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
(63 reference statements)
1
14
0
Order By: Relevance
“…Step width and stance duration show no association with depression in our results, which is in line with previous reports [2], [6].…”
Section: B Abnormal Gait Assisting In Depression Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…Step width and stance duration show no association with depression in our results, which is in line with previous reports [2], [6].…”
Section: B Abnormal Gait Assisting In Depression Analysissupporting
confidence: 93%
“…Besides, slouching posture was often reported in depression [3]- [5]. A recent study on elderly depression suggests that slower gait speed and shorter step length are tied to depression in later life [6]. All these findings indicate that there is an association between depression and gait abnormality.…”
Section: Introductionmentioning
confidence: 94%
“…Disease progression and age are confounding parameters in relating emotions and/or moods to gait characteristics as it has been shown in several studies [1], [32], [48]. Nevertheless, longitudinal studies have confirmed that several differences in gait parameters remain significant even if aging is taken into consideration [76]. Furthermore, differences in response to emotional stimulus due to disease or age are very useful to observe as they reveal underlying neuronal mechanisms that decouples emotions from disease abnormalities [32].…”
Section: B Gait Patterns In Mood Disordersmentioning
confidence: 94%
“…Pieruccini-Faria et al [75] demonstrated that depressive symptoms were associated with increased postural sway in Mild Cognitive Impairment (MCI), which potentially raised the risk of falls. To disentangle the effect of age on gait spatiotemporal parameters in depressed elderly, Briggs et al [76] conducted a four-years longitudinal aging study. The study confirmed that severe symptoms of depression are related to reduced gait velocity and step length compared to age-matched controls.…”
Section: B Gait Patterns In Mood Disordersmentioning
confidence: 99%
“…None of the three studies that analysed the criterion-related validity in motor fitness tests were classified as high quality. Given that the motor fitness tests (i.e., gait/walking speed, balance, timed up and go) are associated with all-cause mortality [114][115][116], falls and fractures [117], disability in activities of daily living [118] and depression [119], it would be useful to know their criterion-related validity.…”
Section: Motor Fitnessmentioning
confidence: 99%